OCULAR WAVEFRONT ABERRATIONS AND OPTICAL QUALITY IN DIABETIC MACULAR EDEMA. Issue 1 (January 2016) - Miháltz, Kata; Kovács, Illés; Weingessel, Birgit; Vecsei-Marlovits, Pia Veronika
Abstract : Purpose: To evaluate optical quality and internal aberrations in patients with diabetic macular edema. Methods: In this prospective study, 33 eyes of patients with diabetic macular edema were scanned with a ray-tracing wavefront device. As a control group, wavefront aberrometry was performed in 31 patients. Ocular and internal aberrations and visual quality metrics were evaluated separately to determine whether the source of aberrations was ocular or internal. Main outcome measures included corrected visual acuities, ocular and internal aberrations, Strehl ratio, and modulation transfer function. Results: There was a statistically significant difference between the groups in internal higher order (HO) root mean square (0.34 ± 0.24 vs. 0.16 ± 0.05), HO Strehl ratio (0.08 ± 0.05 vs. 0.18 ± 0.09), and modulation transfer function (0.29 ± 0.1 vs. 0.4 ± 0.1). There was no statistically significant difference in Strehl ratio and HO root mean square between phakic and pseudophakic patients. Height of cystoid spaces was a significant predictor ( P < 0.001) of Strehl ratio. Besides inner and outer segment integrity, HO Strehl ratio significantly determined best-corrected visual acuity. Conclusion: In eyes with macular edema, internal HO wavefront aberrations were greater than in control eyes. This increase in HO wavefront error seems visually relevant. This study results suggest increased intraretinal edema as the source of HO aberrations. Abstract : Wavefront aberrations and visual quality metrics on patients with macular edema were evaluated using a ray-tracing device. The authors suggest that the elevated internal higher order aberrations origin from the cystoid changes in the retina.